A novel model for predicting a composite outcome of major complications after valve surgery - Cheng, Zhenzhen; Wang, Yishun; Liu, Jing; Ming, Yue; Yao, Yuanyuan; Wu, Zhong; Guo, Yingqiang; Du, Lei; Yan, Min (Frontiers in Cardiovascular Medicine, 2023)
Background: On-pump valve surgeries are associated with high morbidity and mortality. The present study aimed to reliably predict a composite outcome of postoperative complications using a minimum of easily accessible clinical parameters. Methods: A total of 7,441 patients who underwent valve surgery were retrospectively analyzed. Data for 6,220 patients at West China Hospital of Sichuan University were used to develop a predictive model, which was validated using data from 1,221 patients at the Second Affiliated Hospital of Zhejiang University School of Medicine. The primary outcome was a composite of major complications: all-cause death in hospital, stroke, myocardial infarction, and severe acute kidney injury. The predictive model was constructed using the least absolute shrinkage and selection operator as well as multivariable logistic regression. The model was assessed in terms of the areas under receiver operating characteristic curves, calibration, and decision curve analysis. Results: The primary outcome occurred in 129 patients (2.1%) in the development cohort and 71 (5.8%) in the validation cohort. Six variables were retained in the predictive model: New York Heart Association class, diabetes, glucose, blood urea nitrogen, operation time, and red blood cell transfusion during surgery. The C-statistics were 0.735 (95% CI, 0.686–0.784) in the development cohort and 0.761 (95% CI, 0.694–0.828) in the validation cohort. For both cohorts, calibration plots showed good agreement between predicted and actual observations, and decision curve analysis showed clinical usefulness. In contrast, the well-established SinoSCORE did not accurately predict the primary outcome in either cohort. Conclusions: This predictive nomogram based on six easily accessible variables may serve as an “early warning” system to identify patients at high risk of major complications after valve surgery.